THE EFFECT OF WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH INCENTIVES AS INTERVENING VARIABLES (Case Study of Medical Doctor and Nurses in California District) - John Zysman; Alexander (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2020)
This study aims to find out how the influence of work discipline on employee performance with incentives as an intervening variable. The research method used is the method of qualitative data and quantitative data. While the data used is primary data. The data analysis method in this study used simple linear regression analysis to obtain a comprehensive picture of the effect of work discipline variables on employee performance using the SPSS 25 for Windows program. To find out whether there is a significant effect of the independent variable on the dependent variable, a simple linear regression model is used. The results of testing the hypothesis using simple regression analysis and t-test show that: that the t-table value of the Work Discipline variable is 4.074 >